TAHAP PERKEMBANGAN BAHASA ANAK (Tinjauan Neuro-Psikolinguistik) - Akhyar, Fitria (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
The acquisition of a universal child language include: 1) pre-speech, 2) babbling stage, 3) holophrastic, dan 4) combining worlds. Age benchmark in the development stages of language acquisition in children is very relative. That is, at this stage of development neurobiologinya children are able to pronounce certain sounds. At the end of the process and stages of language acquisition, the child can use and understand a large number of sentences, can engage in conversation and find out about the ongoing written language.